Perception of running shoe cushioning: objective and subjective measurements in short-distance running - Keshvari, B.; Schubert, N.; Senner, V.; Mitternacht, J. (Proceedings, 2020)
The aim of this study is to investigate the link between the cushioning feature of running shoes in objective and subjective measurements (OM and SM). In OM, four insoles materials were chosen after impact tests (S1 = 12.6 g, S2 = 7.2 g, G = 11.54 g, and E = 32.41 g). In SM (n = 19), perceived cushioning comfort of insoles was measured using pairwise comparison tests and a Visual analogue scale (VAS) during running. Lower impact peak (IP) leads to greater perceived comfort of cushioning only between S1, S2 and G. But insole E with the highest IP was rated as the most comfortable in cushioning. Its relationship can be explained by associating acceleration magnitudes from the beginning contact to the IP in two possible ways: i) participants did not reach the critical impact peak in SM or ii) participants perceived the critical impact peak, but other factors such as energy rebound and perceived stability influenced their rating in the pairwise comparison tests.